Sistem Cerdas Pemantau Kesehatan Pasien Lanjut Usia Berbasis IoT (Hardware): IoT-based Smart Health Monitoring System for the Elderly (Hardware) - Cahyana, Amelia; Mohammad Yanuar Hariyawan; Wira Indani; Suci Ramadona (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
The Internet of Things (IoT) is a technological innovation that is widely used in science, including the field of health sciences. An intelligent health monitoring system for elderly patients is only one of the IoT applications that might be developed in the field of health sciences. This system must be implemented so that doctors can ascertain the patient's status and that patients can be monitored from home rather than having to visit the hospital for checkups. Therefore, a device is required to make it simpler for patients and medical professionals to check the three vital signs—heart rate, oxygen saturation, and body temperature. Vital signs are a variety of physiological statistical measurements that are used to assess a patient's health state, particularly in elderly people (elderly) who are ill or at risk. With the use of this instrument, the patient can provide the doctor with information on his vital signs, making it simpler for the doctor to identify the patient's condition and treat the patient. This tool's design makes use of the MAX30100 sensor, which measures oxygen saturation and heart rate. Then comes the MLX90614 sensor, which measures body temperature. The microcontroller (ESP32) processes the sensor before sending the data to the MySQL database. The percentage accuracy rate for testing the heart rate is 96.15%, the percentage accuracy level for testing the oxygen level is 97.4%, and the percentage accuracy level for testing the body temperature is 98.3%.